Toxicity evaluations of Papaya seed extract administration in Albino Wistar rats. - Zehra, Nazneen; Naz, Lubna (International Journal of Endorsing Health Science Research, 2020)
Background: Carica papaya seeds are regarded as waste or by-product of the fruit since it is the inedible part of the plant. However, it holds a diversified range of phytochemicals that anticipate their therapeutic role in different types of ailments. The seed extract has been proven for the presence of multiple health benefiting contents and some toxic agents. Studies evaluating the toxicity of the Papaya seed extract are still scarce to support its safe use as a therapeutic agent. Therefore, the undertaken study is to explore the safe dose of the aqueous extract of Papaya seeds. Methodology: This study is designed to examine the toxic potential of Papaya seed aqueous extract on Wistar rats for 42 days by oral administration at dose regimens of 100, 200 and 400 mg/kg body weight in the liver. The groups (n=6) allotted include control untreated and group I (100 mg/kg), group II (200 mg/kg) and group III (400 mg/kg). The liver toxicity was assessed using liver enzymes as toxicity markers. The morphology of liver cells was observed by histology. Results: Our results showed no mortality or signs of toxicity. The body weights were observed to be declining with increasing doses. However, other biochemical parameters displayed no significant alterations in treated groups as compared to the controls. Conclusion: This study supports the evidence that chosen doses of aqueous extract of papaya seeds are safe for normal liver functioning. This evidence endorses the use of the extracts of the seeds as a therapeutic intervention.